JOB SATISFACTION AMONG RESIDENT DOCTORS OF A TERTIARY CARE HOSPITAL IN JAMMU AND KASHMIR (Asian Journal of Medical Research and Health Sciences, 2026)
This study aimed to assess job satisfaction among resident doctors in a tertiary care hospital in Jammu and Kashmir. A structured questionnaire comprising eight domains—Workload, Work–Life Balance, Interpersonal Relationships, Future Career Prospects, Satisfaction with Department, Hospital Infrastructure, Hospital Management, and Salary and Compensation—was administered to 201 participants. Results indicated moderate overall satisfaction, with the lowest scores in Salary and Compensation (1.85) and Hospital management (1.94). Higher satisfaction was seen in Departmental Environment and Hospital infrastructure. Key recommendations include management training, pay restructuring and career development programs.Background: Job satisfaction among resident doctors is a critical determinant of healthcare delivery quality, effective training, retention and overall work efficiency. Understanding the factors influencing their satisfaction can help in improving working conditions and patient outcomes.Objective : To assess the level of job satisfaction and identify key determinants among resident doctors working in a tertiary care hospital in Jammu and Kashmir.Methods: A cross-sectional, descriptive study using a structured questionnaire was conducted among resident doctors of a tertiary care teaching hospital in Jammu and Kashmir. Data were collected using a pre-validated, semi-structured questionnaire covering  8 domains such as workload, work-life balance, supervision, remuneration, and institutional support. Where higher values indicated a higher level of satisfaction. The average scores of items were computed to construct factor scores for each individual. A Chi-square test was applied.Results: The domain-wise mean scores were as follows:Workload: 2.47, Work–Life Balance: 2.60, Interpersonal Relationships: 2.66, Future Career Prospects: 2.70, Satisfaction with Department: 2.74, Hospital Infrastructure: 2.92, Hospital Management: 1.94, Salary and Compensation: 1.85Overall, departmental environment and hospital infrastructure scored highest, while dissatisfaction was most prominent in domains related to salary and hospital management.Conclusion: Resident doctors expressed clear dissatisfaction with systemic aspects such as salary and hospital management. However, stronger intra-departmental support was observed. Addressing the identified gaps through strategic planning and policy changes can enhance job satisfaction and healthcare delivery in the region.